Berani Bicara,Berani Peduli: Aksi Nyata KKN UNP Cegah Bullying Di SD 19 Desa Sijantang Koto, Kota Sawah Lunto - Yummi Meirafoni; Aditya Widya Putri; Mutiara Adila; Tahara Alfitri; Farrel Radilah Arreonsi; Syafri Angga Hendri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Bullying is a serious problem that still frequently occurs in elementary school environments and is often overlooked, despite its significant impact on students’ psychological well-being, self-confidence, social relationships, and academic achievement. As an effort toward early prevention, the 2025 Community Service Program (KKN) of Padang State University (UNP) carried out a concrete initiative entitled “Dare to Speak, Dare to Care” through an anti-bullying campaign at SD Negeri 19, Sijantang Koto Village, Sawahlunto City. This program aimed to foster a culture of empathy, care, and mutual respect among students, while also equipping teachers and school staff with the knowledge and strategies needed to handle bullying effectively. The activities included interactive counseling sessions, educational video screenings, group discussions, role-playing simulations, and the distribution of educational posters and flyers designed to be engaging, age-appropriate, and inclusive. Reflection results indicated an increase in students’ understanding of various forms of bullying as well as greater courage to speak up and care for others. Overall, the program was considered effective and has the potential to serve as a sustainable, school-based bullying prevention model.